Management System in Strengthening Women's Empowerment and Child Protection Institutions in the Child Friendly City Program in Makassar - Auliya Citra; Sangkala Sangkala; Suryadi Lambali; Hasniati Hasniati (Journal La Bisecoman, 2024)
The aim of the research is to strengthen the Women's Empowerment and Child Protection institution in the child-friendly city program in Makassar from management system indicators. This research method uses qualitative methods. The research results show that the role of management is also very important in measuring institutional indicators because when talking about management we will of course always mention resources, budget and organizational culture. At the DP3A institution, human resource capacity building has begun to be carried out by involving and including in training or technical guidance for each staff in accordance with their field and main duties and functions. Meanwhile, in terms of financial management or what is usually called the budget, of course at DP3A it has been accommodated according to its function. Some are aimed at agendas or programs that relate to the KLA, some are aimed at increasing HR effectiveness such as training, and there are also activities related to policy making or the latest innovations.